Ethnographic Study on Changing Regime of Milk Production in Nepal - Gautam, Sahadev; Tharu, Dipak; Pokharel, Saroj (South Asian Journal of Social Sciences and Humanities, 2021)
Agriculture as a by-birth gift to most Nepalese people is the main pillar of the national economy. The milk production system is one of the main segments of Nepalese agriculture. Its regime merely has been providing approximately nine per cent contributions to the national economy. The farming activities of farmers that have been described in this study were not an isolated discourse. This study seeks to find push and pull factors in the milk production regime. Several shreds of evidence and genuine information were described by the respondents about the milk production regime. Using the agrarian and social lenses in this ethnographic work, phenomenological data from nine respondents were collected to examine the existing practice of milk production. This study reflects on the poor condition of milk producers, though they have adopted dairy farms as a strategy of living. The dairy farm has still been a household strategy for rural farmers. It has also been a good local business for income generation and improvement of the socio-economic life of local farmers.